Status and influencing factors of readiness for hospital discharge in patients undergoing radiofrequency ablation for atrial fibrillation (心房颤动射频消融术后患者出院准备度现状及影响因素分析) - LIU Weiwei (刘微微); HUANG Shuping (黄淑萍); ZHONG Bing (钟冰) (中西医结合护理)
Objective To investigate the status of readiness and quality for hospital discharge and its influencing factors in patients undergoing radiofrequency ablation for atrial fibrillation. Methods A total of 151 patients undergoing radiofrequency ablation for atrial fibrillation were collected using convenience sampling method. General data questionnaire, Readiness for Hospital Discharge Scale(RHDS) and Quality of Discharge Teaching Scale (QDTS were used to conduct a questionnaire survey on the subjects. Results The total score of RHDS was(104. 43±15. 57), indicating a high level of readiness for hospital discharge. The total score of QDTS was (159. 56±17. 36), indicating a moderate-to-high level of quality assessment on hospital discharge. The quality of discharge is positively associated with readiness for hospital discharge(r＝0. 777, P＜0. 05). Age, marital status, occupational status, family income, disease occurrence, number of hospitalizations, regular hospital revisit, reduced ability of daily living, Comorbidity of other diseases and type of drug administration. Conclusion Findings of the study showed a high level of readiness and quality for hospital discharge in patients undergoing radiofrequency ablation for atrial fibrillation. Patients’ awareness of readiness for hospital discharge is correlated with quality for hospital discharge. Medical workers should take effective intervention to improve quality of hospital discharge teaching and quality of life after hospital discharge (目的 探讨心房颤动患者射频消融术后出院准备度及出院指导的现状及其相关影响因素。方法 随机抽取2022年1月—8月在医院接受房颤射频消融术治疗的患者151例作为研究对象。采用一般资料调查问卷、出院准备度量表(RHDS)和出院指导量表(QDTS)对151例研究对象进行调查。结果 患者RHDS量表总分为(104. 43±15. 57)分, 处于较高的水平; QDTS量表得分(159. 56±17. 36)分, 处于中等水平。出院指导质量与出院准备度呈正相关(r＝0. 777, P＜0. 05)。年龄、婚姻状况、工作状态、家庭人均收入、发病情况, 疾病住院次数、定期多次复诊、生活自理能力下降、合并其他疾病与服用药物种类是影响患者出院准备度的因素。结论 心房颤动患者射频消融术后出院准备度和出院指导质量处于较高水平, 且心房颤动患者对出院准备度的感知与其获得的出院指导质量关系密切。医务人员要找寻切实可行的措施提高指导质量, 对出院指导进行有效的干预, 从而可改善患者出院后的生活质量, 进而提高患者的出院准备水平。)